Подходы к анализу рисков реализации комплексных инновационных проектов в авиастроении (Путеводитель предпринимателя)
The basic tendencies of development of aircraft engineering in Russia are considered, the problems of the industry are established. The necessity of management of risks of complex innovative projects is shown and the approach of estimation of their magnitude is offered.